Federal Regulation of the Food Industry: Part 2, Federal Regulatory Agencies - Ronald H. Schmidt; Douglas L. Archer; Michael T. Olexa (EDIS)
This document provides a general overview of federal government organizations with emphasis on those agencies involved with the regulation of the food industry. This document is FSHN05-11, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June 21, 2005.